Analisis Faktor-Faktor Yang Mempengaruhi Kemiskinan Di Desa Takarai Kabupaten Malaka - Kamilaus Konstanse Oki; Maria Yanti Akoit; Helena Bubu (Ekopem: Jurnal Ekonomi Pembangunan, 2020)
Poverty is the inability of society to meet basic needs and other needs. The majority of Takarai villagers are classified as poor. Natural resource factors, human resources, and infrastructure are not only contributors to community poverty but also the complexity of the problem. The capacity of the government as a protector to bring people out of poverty is still very limited. The side effects of poverty are the lack of formal education levels at a higher level, less nutrition and stunting, maternal and infant mortality rates, and a higher government burden for social assistance.